Effectiveness of the MetSLIM lifestyle intervention targeting individuals of low socio-economic status and different ethnic origins with elevated waist-to-height ratio. Issue 14 (24th July 2017) - Bukman, Andrea J; Teuscher, Dorit; Meershoek, Agnes; Renes, Reint Jan; van Baak, Marleen A; Feskens, Edith JM
Abstract: Objective: To evaluate whether the lifestyle intervention MetSLIM targeting individuals of low socio-economic status of Turkish, Moroccan and Dutch origin was successful in improving waist circumference and other cardiometabolic risk factors, lifestyle behaviour and quality of life. Design: A quasi-experimental intervention study (Netherlands Trial Register NTR3721). The intervention group participated in a 12-month combined dietary and physical activity programme. Examinations were performed at baseline and after 12 months. Participants underwent anthropometric measurements and blood withdrawal, and completed questionnaires on dietary intake, physical activity and quality of life. Setting: Socio-economically deprived neighbourhoods in two Dutch cities, involving non-blinded ethnicity-matched and gender-matched research assistants, dietitians and sports instructors. Subjects: Mainly Turkish (49 %) and Dutch (36 %) subjects, aged 30–70 years, with a waist-to-height ratio of >0·5 (intervention, n 117; control, n 103). Dropout was 31 %. Results: At 12 months, the intervention group showed greater improvements than the control group in waist circumference ( β =−3·3 cm, 95 % CI −4·7, −1·8, P <0·001) and other obesity measures. Additionally, greater reductions were observed for total cholesterol ( β =−0·33 mmol/l, 95 % CI −0·56, −0·10, P =0·005) and LDL cholesterol ( β =−0·35 mmol/l, 95 % CI −0·56, −0·14, P =0·001). Dietary changes were significant for fibre intake ( β =1·5 g/4184 kJ (1000 kcal), 95 % CI 0·3, 2·7, P =0·016). Compared with the control group, the intervention group reported a decrease in total minutes of physical activity ( β =−573 min/week, 95 % CI −1126, −21, P =0·042) and showed improvements in the quality-of-life domains 'health transition' and 'general health'. Conclusions: MetSLIM was shown to be effective in improving waist circumference, total and LDL cholesterol, and quality of life among Dutch and Turkish individuals living in deprived neighbourhoods.